Recreational drug use among Chinese MSM: results from a national-wide cross-sectional study. (October 2016) - Zhao, Peizhen; Tang, Songyuan; Wang, Cheng; Zhang, Ye; Best, John; Huang, Shujie; Yang, Bin; Wei, Chongyi; Tang, Weiming; Tucker, Joseph D
Abstract: Background: In the past decade, recreational drug use has considerably increased among Chinese men who have sex with men (MSM). This increase has a great potential to worsen the scenario of the heavy burden of HIV among Chinese MSM. This study aimed to investigate the prevalence of recreational drug use, and to explore the association between poppers use and testing history for HIV or STIs, gay app use, and other sexual behaviours. Methods: We recruited MSM who were born male and were aged 16 years or older through a nation-wide online survey in 2014. We collected information regarding socio-demographics, risk behaviours, recreational drug use, sexual orientation, testing history for HIV and other STIs, and gay app use. We did univariate and multivariate analyses to determine factors associated with recreational drug use among Chinese MSM. Written informed consent was gained from each participants, and the ethical approval was obtained from institution review committees in China and the United States. Findings: Among 1424 participating MSM, 1100 (77%) had used any recreational drugs in their life-time. In the past 12 months, 303 (21%) had used poppers, 34 (2%) had used crystal meth, and 15 (1%) had used ecstasy. The mean age of all participants was 25·6 years (SD 6·8), 1038 (73%) were self-identified as gay, 588 (41%) were students, and 1194 (84%) had never been married. Multiple logistic regression revealed that compared with non-poppers users, poppers users were more likely to have been tested for HIV (adjusted odds ratio [aOR]=1·50, 95% CI 1·15–1·96) and for other STIs except HIV (1·65, 1·26–2·17). Additionally, poppers users were more likely to engage in group sex (2·63, 1·80–3·86) or in commercial sex (1·86, 1·13–3·06), and to use gay apps for partner seeking (2·10, 1·58–2·80). Interpretation: High-risk MSM in China have a high rate of recreational drug use. Public health programmes serving MSM may consider integration of interventions to decrease harms associated with recreational drug use. Funding: This work was supported by National Institutes of Health (National Institute of Allergy and Infectious Diseases 1R01AI114310 to JT and CW); UNC-South China STD Research Training Centre (Fogarty International Centre 1D43TW009532 to JT); UNC Center for AIDS Research (National Institute of Allergy and Infectious Diseases 5P30AI050410 to JT); University of California San Francisco Centre for AIDS Research (National Institute of Allergy and Infectious Diseases P30 AI027763 to CW); National Institute of Mental Health (R00MH093201 to CW); the UNC Chapel Hill, Johns Hopkins University, Morehead School of Medicine and Tulane University (UJMT) Fogarty Fellowship (FIC R25TW0093 to WT). This publication was also supported by Grant Number UL1TR001111 from the National Center for Advancing Translational Sciences (NCATS) at the National Institutes of Health. These funders played no role in any step of this study.